Occupational Therapy Students' Perspectives on Using Virtual Reality Simulation in Preparation for Objective Structured Clinical Examinations: A Qualitative Study. - Firouzeh, Pegah; Jean, Craig R. St.; Ha, Christine; Roberts, Mary Roduta (Open Journal of Occupational Therapy (OJOT))
The use of virtual reality (VR) simulations in clinical education has been receiving increased research attention. The purpose of this study was to investigate first-year occupational therapy (OT) students' experiences using a VR-simulated clinical interview as part of their preparation for a client history-taking Objective Structured Clinical Examination (OSCE). This qualitative study used focus groups to understand students' (n = 20) perceptions of the effect of VR simulation on learning and exam readiness. We also explored students' perceptions of the simulation's authenticity, strengths, and weaknesses. Qualitative data analysis was conducted to identify codes and develop categories in association with the study's objectives. Students expressed mixed perceptions of the VR simulations, acknowledging its realism in some respects and technological limitations in others. While many participants had challenges navigating the virtual environment and were frustrated by the simulated patient's limited capacity for dialogue, their reflections indicated that VR presented an opportunity to adjust their communicative approach to suit the circumstances of the simulation, fostering their adaptability and capacity for stress management. Our findings, namely that VR can provide a novel and approachable platform for students to hone their skills, support the use of virtual simulations in OT education.